To explore the molecular mechanism of IRF7 involved in acute kidney injury in sepsis based on proteomics - Li Xiang; Ma Wanli; Song Jiannan; Hu Zhanfei; Zhou Qi; Li Haibo (Proteome Science)
Abstract Background Acute kidney injury is a common complication of sepsis, and its mechanism is very complicated. The purpose of this study was to investigate the mechanism of key differentially expressed proteins and their related signaling pathways in the occurrence and development of acute kidney injury in sepsis through proteomics. Methods Acute kidney injury was induced by intraperitoneal injection of lipopolysaccharide at 10 mg/kg. Renal tissues were analyzed by TMT quantitative proteomic analysis. Differentially expressed proteins (DEPs) were screened. Gene Ontology (GO) function analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis and protein-protein interaction (PPI) network analysis were performed. Results We obtained 530 DEPs. GO analysis showed that the biological process of DEPs was mainly stress response. The molecular functions of DEPs mainly focus on catalytic activity. The cellular components of DEPs were mainly located in the intracellular and cytoplasm. KEGG analysis showed that DEPs were mainly involved in metabolic pathways. Ten key proteins with interaction degree, such as Isg15, Irf7, Oasl2, Ifit3, Apob, Oasl, Ube2l6, Ifit2, Ifih1 and Ifit1 were identified. Irf7 was significantly up-regulated in rat kidney tissues. Conclusion The upregulation of Irf7 plays an important role in the mechanism of acute renal injury induced by sepsis.